Swinging Before Śiva: Renunciation, Colonialism and a Bengali Ritual. - De, Aniket. (Tufts University. Tisch Library., 2014)
Tisch Library Undergraduate Research Award Winner, 2014.  This paper studies the ritual of Gājan or “hook-swinging”, a common practice in colonial Bengal. The ritual was a show of magical power gained by undertaking asceticism and worshipping the god Śiva; devotees showed the ability to swing unsupported from high poles. The British were disturbed by the ritual in the nineteenth century, and banned it in the 1860s. In this paper, I first study how a discourse on hook-swinging being a deviant low-caste practice was actively constructed by both British and the Indian urban middle class in the 1830s. Such discourses represented hook-swinging as a transgression of Hinduism. I finally show that a much more nuanced way to look at the ritual is to see it as what I call “temporary renunciation”. Small localised rituals like hook-swinging drew on and, in turn, influenced larger religious ideologies like renunciation and asceticism, and the householder-renouncer dichotomy. Recognizing that our understanding of many rituals has largely been through the colonial lens will help us develop more sophisticated understandings of the relationship of ritual, religious ideologies and colonialism.